A New Validated RP- HPLC Method for the Determination of Nevirapine in Human Plasma - C. H. Venkata Kumar; D. Ananth Kumar; J. V. L. N. Seshagiri Rao (E-Journal of Chemistry)
A rapid, selective and sensitive high performance liquid chromatographic method for the estimation of nevirapine in human plasma has been developed. Chromatography was carried out on a Hypersil BDS C18 column using a mixture of ammonium acetate buffer (pH 4.0 ± 0.05) and acetonitrile (85:15 v/v) as the mobile phase. The eluents were monitored for the drug by UV detection at 254 nm. Oxcarbazepine was used as an internal standard for this study. The retention times for nevirapine and oxcarbazepine were found to be 7.2 and 14.7 min respectively. The method was found to be linear in the concentration range of 50 ng/mL to 5003.7 ng/mL. The method was validated as per FDA guidelines and was found to be suitable for bioequivalence and pharmacokinetic studies.